Periodontal referral pattern in periodontal specialist clinic in faculty of dentistry, Universiti Teknologi MARA (UiTM): a retrospective pilot study - Noor, Erni; Noor Kamaruzaman, Nur Azielyana; Mohd Jeffri, Nur Syahira; Nik Eezammudden, Nik Nazurah; Mohd Noh, Nur Zety (2018)
Objectives: Periodontitis is a chronic disease which remain undiagnosed and untreated without proper examination and referral to specialist clinic for further management Therefore, this study was conducted to evaluate the pattern of referrals to Universiti Teknologi MARA (UiTM) Periodontal Specialist Clinic. Materials and methods: A total of 176 periodontal cases referred to UiTM Periodontal Specialist Clinic in year 2011 and 2016 were identified and patient’s referral forms were collected. The data obtained were the referred cases from undergraduate student clinics, other specialist clinics, UiTM primary dental care clinic and private dental clinics. Descriptive data analysis was conducted using frequency distribution by SPSS. Chi square analysis was used to evaluate the association of source of referral, diagnosis and reason for referrals to Periodontal Specialist Clinic. Results: There was increased referral cases to Periodontal Specialist Clinic in 2016 (86.9%) compared to 2011 (13.1%). Most referral to Periodontal Specialist Clinic were received from faculty’s undergraduate student clinic in both 2011 and 2016 (46%), followed by other specialists (27.3%), primary care clinic (25.6%) and private practice (1.1%). 96% of cases were referred for intervention by periodontist as more than half of the cases were referred for the non-surgical periodontal treatment. Chi square analysis showed the association between source of referral and reason for referral was statistically significant (p value=0.000). Conclusion: Proper periodontal screening in all patients and necessary referral to specialist clinic is crucial to prevent undiagnosed periodontal disease.